Sifat Fisik dan Penerimaan Roti Tawar dari Tepung Komposit Terigu dan Singkong dengan Variasi Lama Pencampuran Adonan - Rusdin Rauf; Khasanah Tri Andini (agriTECH, 2019)
This study was aimed to find out the physical characteristics and sensory acceptance of bread made from different variations of wheat and cassava composite flour ratio, and the dough’s mixing duration. The research was conducted experimentally with 4 ratio variations of wheat and cassava flours, namely 100:0, 90:10, 80:20 and 70:30, and 3 variations of dough mixing duration, namely 10 minutes, 15 minutes and 20 minutes. The analyzed parameters for dough were the development and the elongation, and for bread were the development, hardness, elasticity, and acceptance. The results showed that the higher the cassava flour proportion, the lower the level of dough development. The dough development was affected by mixing duration, but there was no increasing tendency of the cassava flour. The treatment of 100:0 (15 minutes), which was not significantly different from 90:10 (15 minutes), indicated the highest dough development. The higher the cassava flour proportion, the lower the dough’s tensile strength and the strain, while the mixing duration showed the influence on the dough’s tensile strength and strain. Both indicators gave the same highest point, it was the treatment of 100:0 (15 minutes). The bigger the cassava flour proportion, the lower the bread development. The highest bread development was given by 100:0 treatment, but there was no effect of mixing time on this treatment. The bigger the cassava flour proportion, the higher the bread’s hardness, while for the bread’s elasticity, it showed the opposite, the higher cassava flour, the lower the bread’s elasticity. The two bread texture indicators were influenced by the mixing time but did not provide a steady tendency toward the increasing proportion of cassava flour. The highest bread hardness was indicated by the 70:30 treatment, while the biggest bread elasticity was with the treatment of 100:0. The highest acceptance of bread was revealed by 100:0 treatment, which was not significantly different from 90:10 treatment.